Assessment of potentially toxic elements pollution in soils and plant leaves along the high-traffic highway zones in Tehran, Iran - Mahdieh Hosseinzadeh; Hamid Toranjzar; bbas Ahmadi; Nourollah Abdi; Javad Varvani (Anthropogenic Pollution)
The accumulation of potentially toxic elements (PTEs) in roadside soils and plant leaves due to vehicular emissions presents significant environmental and public health risks, particularly in densely populated urban areas. This study evaluated the concentrations of five PTEs—copper (Cu), lead (Pb), nickel (Ni), cadmium (Cd), and zinc (Zn)—in soils and leaves of three urban plant species (Pine, Cypress, and Mulberry) across six highways in Tehran, Iran, categorized into high, medium, and low-traffic zones. Soil samples were collected at a depth of 0–30 cm, and leaf samples were obtained from the canopy's outer sections. Samples were digested with aqua regia (soil) and nitric-hydrochloric acid (leaves) and analyzed using atomic absorption spectrophotometry. Pollution indices, including Pollution Load Index (PLI), Transfer Factor (TF), and Bioaccumulation Factor (BCF), were applied to assess contamination levels and metal mobility.The results showed moderate pollution levels across high-traffic zones (PLI = 3.94), with cadmium (Cd) contributing the most significant ecological risk (RI = 154.50). Transfer Factor (TF) analysis revealed high bioavailability for zinc (TF = 0.78) and lead (TF = 0.81), while cadmium exhibited limited uptake by plants (TF < 0.004). Bioaccumulation Factor (BCF) calculations indicated Pine and Cypress species had higher potential for metal uptake, with BCF values exceeding 1 for zinc and lead in high-traffic areas, whereas Mulberry demonstrated relatively lower accumulation. Despite a normalized NIPI index value of 1, the enrichment factor (EF) for zinc (EF = 98.04) underscores significant anthropogenic contributions, particularly from non-exhaust vehicular emissions. These findings highlight the need for ongoing monitoring, effective traffic management, and remediation strategies to address heavy metal pollution in urban environments.